2007
DOI: 10.1111/j.1440-1681.2007.04787.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Reduction of Lifestyle‐related Diseases in Young Adults on Soy‐ or Fish‐rich Traditional Japanese Meals

Abstract: 1. One hundred and sixty-four female junior college students aged 18 -24 were randomized into three groups, with each group consuming a specified lunch for 5 weeks: group C (ordinary school lunch; K ), group S (K + soy-rich lunch containing more than 40 mg soy isoflavones) and group F (K + fish containing more than 700 mg DHA).2. Of the 157 subjects who completed the study (46 from group C, 54 from group S and 57 from group F ), triglycerides (TG) in subjects of S and F groups were significantly decreased from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Only few randomized controlled trials (RCTs) assessed the influence of whole fish, and therefore a combination of fish oil and fish protein, on weight loss. These studies showed a similar effect of whole fish compared to fish oil, even when lean fish was used, suggesting a potential role of fish protein in weight loss . To date, no meta‐analysis on this subject has been carried out.…”
Section: Introductionmentioning
confidence: 92%
“…Only few randomized controlled trials (RCTs) assessed the influence of whole fish, and therefore a combination of fish oil and fish protein, on weight loss. These studies showed a similar effect of whole fish compared to fish oil, even when lean fish was used, suggesting a potential role of fish protein in weight loss . To date, no meta‐analysis on this subject has been carried out.…”
Section: Introductionmentioning
confidence: 92%
“…Whale meat is also characterized by its rich content of the free amino acid balenine, which is recognized for its antifatigue effects [ 14 ]. Although Japanese people today do not eat whale meat because of food shortage, as they did in the past, diets containing whale meat are expected to contribute to dietary diversity and maintain and improve health [ 15 , 16 ]. The consumption of whale meat is also expected to improve Japan's low food self-sufficiency ratio (currently approximately 39 %) and act as a substitute for meat, which is expected to become scarce in the future owing to the predicted global food crisis [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%